Immune response and resistance to Rous sarcoma virus challenge of chickens immunized with cell-associated glycoproteins provided with a recombinant avian leukosis virus. - Chebloune, Y (1991)
The Rous-associated virus 1 env gene, which encodes the envelope gp85 and gp37 glycoproteins, was isolated and inserted in place of the v-erbB oncogene into an avian erythroblastosis virus-based vector, carrying the neo resistance gene substituted for the v-erbA oncogene, to generate the pNEA recombinant vector. A helper-free virus stock of the pNEA vector was produced on an avian transcomplementing cell line and used to infect primary chicken embryo fibroblasts (CEFs) or quail QT6 cells. These infected cells, selected with G418 (CEF/NEA and QT6/NEA, respectively) were found to be resistant to superinfections with subgroup A retroviruses. The CEF/NEA preparations were used as a cell-associated antigen to inoculate adult chickens by the intravenous route compared with direct inoculations of NEA recombinant helper-free virus used as a cell-free antigen. Chickens injected with the cell-associated antigen (CEF/NEA) exhibited an immune response demonstrated by induction of high titers of neutralizing antibodies and were found to be protected against tumor production after Rous sarcoma virus A challenge. Conversely, no immune response and no protection against Rous sarcoma virus A challenge were observed in chickens directly inoculated with cell-free NEA recombinant virus or in sham-inoculated chickens.